RURAL HOUSEHOLDS IN UKRAINE: CURRENT STATE AND TENDENCIES - Serhiy, Moroz (Economics of Agriculture, 2013)
Households are primary means of survival for rural people of Ukraine under conditions of limited employment and income-earning opportunities in the countryside. In this paper, main tendencies of development of rural households are analyzed. Particular attention is given to socio-demographic characteristics, agricultural production activities, and changes in incomes and expenditures of the household sector. Further possible scenarios of development of households are considered.